2013
DOI: 10.1097/igc.0b013e318291e8ca
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns, Health Care Utilization, and Costs of Ovarian Cancer in Central and Eastern Europe Using a Delphi Panel Based on a Retrospective Chart Review

Abstract: Patients with ovarian cancer consume considerable health care resources and incur substantial costs in Central and Eastern Europe. These findings may prove useful for clinicians and decision makers in understanding the economic implications of managing ovarian cancer in Central and Eastern Europe and the need for innovative therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Over threequarters of the study population, however, was older than 70 years, and costs related to departure from the workforce may be trivial as well as insignificant from a third-party payer perspective. Unlike previous studies that have reported costs for only a fixed duration [51,52], we accounted for censoring to give an estimate of lifetime costs related to treating advanced ovarian cancer and also adjusted costs for patient and clinical characteristics. Studying lifetime treatment cost is particularly relevant in this cohort because of the high tumor recurrence rate, which may necessitate continual chemotherapeutic treatment in the continuous phase of care and contribute substantially to the overall cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over threequarters of the study population, however, was older than 70 years, and costs related to departure from the workforce may be trivial as well as insignificant from a third-party payer perspective. Unlike previous studies that have reported costs for only a fixed duration [51,52], we accounted for censoring to give an estimate of lifetime costs related to treating advanced ovarian cancer and also adjusted costs for patient and clinical characteristics. Studying lifetime treatment cost is particularly relevant in this cohort because of the high tumor recurrence rate, which may necessitate continual chemotherapeutic treatment in the continuous phase of care and contribute substantially to the overall cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive surveillance and many cycles of chemotherapy (maintenance or recurrence) could potentially drive high costs in this phase. Cost studies in Europe and Australia have estimated chemotherapeutic costs as the prime component of total costs when treating ovarian cancer [51,52]. Thus, when dealing with censored observations, studying lifetime costs becomes important to estimate overall disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Women with ovarian cancer consume a large proportion of healthcare resources 20 . Bangladesh has developed a pluralistic healthcare system, which includes government services, multiple NGOs and robust private sector 21 .…”
Section: Discussionmentioning
confidence: 99%
“…complex care our patients received 22 . Development of universal healthcare insurance must be part of the strategy in Bangladesh for complex care such as ovarian cancer 23,20 .…”
Section: Casementioning
confidence: 99%
“…Cost-of-illness analyses of the key prosperity diseases remain rather infrequent in Eastern Europe and the Balkans region (1). Over the past decade, a few pioneering assessments were published, laying the ground for the informed decision making of local health policymakers (2).…”
Section: Introductionmentioning
confidence: 99%